2011
DOI: 10.1016/j.jss.2010.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Disease in Trauma and Surveillance Ultrasonography

Abstract: Our preliminary data argue against the use of routine duplex surveillance of lower extremities for DVT in trauma patients. A larger, prospective analysis is necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
0
23
1
1
Order By: Relevance
“…They concluded that this two-step screening strategy, as opposed to universal duplex for all patients, was effective in discovering DVTs that were carried over from acute care hospitals. The rationale against screening is not based on its inability to detect occult DVT; in fact, Jawa et al [14] pointed out that three investigations using the National Trauma Data Bank showed that higher rates of surveillance lead to a higher rate of DVT diagnosis. It is the uncertain clinical significance of finding an occult DVT that is the foundation of recommendations against screening practices.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that this two-step screening strategy, as opposed to universal duplex for all patients, was effective in discovering DVTs that were carried over from acute care hospitals. The rationale against screening is not based on its inability to detect occult DVT; in fact, Jawa et al [14] pointed out that three investigations using the National Trauma Data Bank showed that higher rates of surveillance lead to a higher rate of DVT diagnosis. It is the uncertain clinical significance of finding an occult DVT that is the foundation of recommendations against screening practices.…”
Section: Discussionmentioning
confidence: 99%
“…In major trauma patients, screening for asymptomatic DVT has definitely been shown to detect more thrombi (Winemiller, 1999;Furlan, 2007;Pierce, 2008;Haut, 2009;Azarbal, 2011;Jawa, 2011;Dietch, 2015). Similarly, among acute SCI patients managed at the Mayo Clinic from 1976 to 1995, the use of DVT screening was the strongest predictor of a VTE diagnosis, with a risk ratio of 2.8-fold compared with patients not screened (Winemiller, 1999).…”
Section: We Suggest That Sci Patients Not Be Routinely Screened With mentioning
confidence: 97%
“…These studies demonstrate that routine screening will detect more asymptomatic DVTs but does not reduce symptomatic thromboembolic events. Implementation of a routine DVT surveillance program in the trauma service at the University of Nebraska Medical Center resulted in a fivefold increase in the number of DUS studies performed with no significant reduction in PE (Jawa, 2011). Three additional trauma studies reported that routine screening provided no incremental protection over early use of appropriate thromboprophylaxis (Schwarcz, 2001;Haut, 2007).…”
Section: We Suggest That Sci Patients Not Be Routinely Screened With mentioning
confidence: 99%
See 2 more Smart Citations